DEVELOPMENT OF EMPATHETIC MANAGERS TO SUPPORT DISABLED EMPLOYEES UTILIZING SIMULATION-BASED LEARNING - Hobbs, Eugene (East Carolina University)
Empathy is a crucial skill for effective leadership, particularly in diverse workplaces where understanding and addressing employees’ needs contribute to organizational success. This study examines the impact of simulation-based learning on developing empathy in business students. Grounded in Kolb’s experiential learning theory (1984), the research explores how immersive simulations enhance students' empathy by engaging them in real-world workplace scenarios. A mixed-methods approach was used to assess the effectiveness of simulation-based empathy training. Undergraduate business management students participated in a simulation addressing mobility challenges, reflecting on accommodations for employees with disabilities. Pre- and post-tests measured changes in empathy levels, while qualitative responses provided deeper insights into students' perspectives. The results showed a significant increase in self-reported empathy scores (p = 0.015), with participants demonstrating an improved ability to recognize and respond to employees’ emotional needs. Qualitative findings further indicated a heightened awareness of inclusive leadership and a stronger commitment to fostering supportive work environments. This study affirms the value of simulation-based learning in developing empathy among future managers. Findings highlight how Kolb’s experiential learning cycle—encompassing concrete experience, reflective observation, abstract conceptualization, and active experimentation—effectively enhances emotional intelligence in management education. While the simulations fostered short-term empathy growth, future research should investigate long-term skill retention. Additionally, expanding simulations to include other diversity factors, such as race, gender, and socioeconomic status, could further promote empathy and inclusivity in leadership training.
Keywords: Business Administration, Management; Education, Business; Aging; Organization Theory